Clima organizacional y su influencia en la satisfacción laboral de los trabajadores de la empresa Agrorgsa S.A., Quevedo año 2023. - Mero Sacon, Shirley Auxiliadora (2025)
This study was conducted at Agrorgsa S.A., located in Quevedo, Los Ríos province. The company specializes in the manufacture and distribution of chemical products for the agricultural sector and is recognized for its commitment to sustainable solutions and regional development. The main objective was to analyze the organizational climate and its influence on job satisfaction among employees in the year 2023. To achieve this, a mixed-methods approach was applied, integrating both quantitative and qualitative methods. Techniques such as surveys were used for quantitative data collection, and interviews were conducted to explore qualitative aspects. The data were processed using statistical tools to facilitate interpretation through tables and graphs.